A true expert knows which question should be asked. - Eddie Dekel; Yossi Feinberg (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2004)
We suggest a test for discovering whether a potential expert is informed of the distribution of a stochastic process. In a non-Bayesian non-parametric setting, the expert is asked to make a prediction which is tested against a single realization of the stochastic process. It is shown that by asking the expert to predict a small set of sequences, the test will assure that any informed expert can pass the test with probability one with respect to the actual distribution. Moreover, for the uninformed non-expert it is impossible to pass this test, in the sense that or any choice of a small set of sequences, only a small set of measures will assign a positive probability to the given set. Hence for most measures, the non-expert will surely fail the test. We define small as category 1 sets, described in more detail in the paper.
Keywords: D83; C14; C50; 330; Asymmetrische Information; Informationsverhalten; Sachverständige; Informationsökonomik